Breeding and deploying high-zinc maize in the tropics - Boddupalli, Prasanna; Palacios Rojas, Natalia; San Vicente Garcia, Felix; Dhliwayo, Thanda; Menkir, Abebe; Ndhlela, Thokozile; Nair, Sudha; Zhang, Xuecai (Springer Cham, 2025)
High-zinc maize offers a promising solution to alleviate this micronutrient malnutrition, particularly in the Global South. Maize, as a C4 crop, shows potential in addressing declining zinc levels in the face of environmental stressors, but achieving optimal zinc concentrations in maize kernels requires targeted breeding efforts. This chapter highlights the genetic variability of kernel zinc concentration in maize germplasm, considering the complexities of trait inheritance and the influence of genotype-environment interactions. Conventional breeding strategies, alongside modern tools such as QTL mapping, genome-wide association studies (GWAS), and genomic selection (GS), have been instrumental in developing high-zinc varieties. Data from efforts in Latin America and Africa reveal that these varieties can perform competitively in terms of yield and agronomic traits. The bioavailability of zinc in biofortified maize is discussed, alongside the nutritional benefits it provides, particularly in traditional maize-based diets. Key challenges, such as potential yield penalties and the need for consumer acceptance, are explored, with emphasis on combining nutritional improvement with essential agronomic traits like disease resistance and yield stability. The broader opportunities for scaling high-zinc maize are also considered, underscoring the role of collaborative efforts and public-private partnerships in ensuring the sustainable adoption of these nutritionally enhanced varieties.